Problem nieśmiałych młodzieńców, czyli ‘vitiosa verecundia’ - Sowa, Joanna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
Both Greeks and Romans considered shame an important instrument of moral education. However, while respect for elders and superiors was a desirable trait of young people, it could also turn sometimes into a serious character flaw – excessive compliance with all who made any demands, even the wrong ones. Therefore, shyness was often considered ‘a disease of the soul’ as a feeling that made one feel ashamed to do the right thing. In the article, the concept of vitiosa verecundia is presented on the basis of texts by Seneca, Aristotle, Quintilian, Livy and, above all, Plutarch’s treatise De falso pudore.